Supply chain risk assessment with the functional quantification of lead time deviation. (6th July 2010) - Buscher, Udo; Wels, Andreas
The Supply Chain Risk Management (SCRM) is gaining an increasing interest. An overview about scientific papers in this area of investigation reveals a lack of methods assessing the Supply Chain (SC) risk. This paper identifies the lead time deviation as an appropriate variable to describe SC risk. We present a model which is able to quantify the immanent risk of all members of any SC in functional form.